A Quaint & Curious Volume - Rogers, Dylan K. (Archaeopress Publishing, 2021)
John J. Dobbins, Professor of Roman Art and Archaeology, taught at the University of Virginia in the Department of Art from 1978 until his retirement in 2019. His legacy of research and pedagogy is explored in A Quaint & Curious Volume: Essays in Honor of John J. Dobbins. Professor Dobbins' research in the field of Roman art and archaeology spans the geographical and chronological limits of the Roman Empire, from Pompeii to Syria, and Etruria to Spain. This volume demonstrates some of his wide-reaching interests, expressed through the research of his former graduate students. Several essays examine the city of Pompeii and cover the topics of masonry analysis, re-examinations of streets and drains, and analyses of the heating capacity of baths in Pompeii. Beyond Pompeii, the archaeological remains of bakeries are employed to elucidate labor specialization in the Late Roman period across the Mediterranean basin. Collaborations between Professor Dobbins and his former students are also explored, including a pioneering online numismatic database and close examination of sculpture and mosaics, including expressions of identity and patronage through case studies of the Ara Pacis and mosaics at Antioch-on-the-Orontes. A Quaint & Curious Volume not only demonstrates John Dobbins' scholarly legacy, but also presents new readings of archaeological data and art, illustrating the impact that one professor can have on the wider field of Roman art and archaeology through the continuing work of his students.